Diverticulitis of the small bowel, an unusual cause of inflamatory acute abdomenAbstract in English - Stefani Leão, Ari Ben-Hur (2012)
AIMS: To describe the clinical presentation, differential diagnosis and treatment of a case of diverticulitis of the small intestine. CASE DESCRIPTION: A man of fifty-eight years of age presented a clinical picture of abdominal pain and distension, with imaging demonstrating thickened loop of small intestine. Direct laparoscopic examination of the abdomen diagnosed diverticulitis of the small intestine, which received surgical treatment. The patient progressed well postoperatively. CONCLUSION: Small bowel diverticular disease is an uncommon condition and its great clinical importance lies in its presentation with problems such as perforation, obstruction and bleeding, which makes it difficult to establish a differential diagnosis with other abdominal diseases.